9th Educational, Innovation, Creativity & Design Competition (EICD 2018) / E. Tavasuria Elangovan - Elangovan, E. Tavasuria (Corporate Communication Unit, Universiti Teknologi MARA, Perak Branch, 2018)
This educational programme has captured the interest of school students, local university students as well as international students. The group members are Siti Nurrehan Bt Mohd Bas-ri, Nur Syahirah Binti Rahim, Rabiatul Adawiyah Binti Abdul Wahab, Lili Widarti Binti Zainuddin, Maryam Binti Mohammad as well as Mazlini Binti Mazlan and were supervised by supervi-sor and co-supervisor, Rabiatul Adawiyah Binti Abdul Wahab and Lili Widarti Binti Zainuddin who are currently FSG lecturers at UiTM Perak Branch, Tapah Campus. Several talented stu-dents were selected to participate in the IIDEX competition at UiTM Shah Alam which will take place in September 2018.